Application of platelet-rich fibrin in endodontic surgery: a pilot study - Daniele Angerame; Matteo De Biasi; Iva Kastrioti; Vittorio Franco; Attilio Castaldo; Michele Maglione (Ariesdue, 2015)
Aim: To assess preliminarily the potential benefits of the use of the platelet-rich fibrin (PRF) in modern endodontic surgical procedures in terms of radiographic healing acceleration and postoperative discomfort reduction. Methodology: Eleven patients with chronic apical periodontitis were randomly assigned to either the PRF (n = 7) or the control group (n = 4). Postoperative swelling and pain were assessed with a questionnaire. Radiographic healing was scored according to Molven's scale up to a period of one year. Data were statistically analyzed with non-parametric tests. Results: In the PRF group the patients experienced less pain in the 2-6 h postoperatively as well as oedema, which never exceeded the moderate intraoral swelling. Radiographic healing was detectable earlier in the PRF group, with the majority of cases scored as complete healing after 2-3 months. Conclusions: The adjunctive use of PRF might promote the acceleration of the radiographic healing and reduce the postoperative discomfort.